Leadership And Entrepreneurial Ethics In Islamic Education - UNZIL AL HUDA; GHEITSAA' ZAAHIRA SHOOFIYA (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
This study examines the synergy between leadership and entrepreneurial ethics in Islamic education as a strategy to improve the quality of educational institution management. Leadership from an Islamic perspective emphasizes not only the ability to organize and direct, but also requires exemplary conduct, trustworthiness (amanah), and justice in managerial processes. Meanwhile, entrepreneurial ethics based on Islamic values stress honesty, halal practices, responsibility, and excellent service in all economic activities. The integration of these two aspects can be observed in Islamic schools through the development of entrepreneurship programs managed professionally while remaining grounded in spiritual values, such as student cooperatives, skills training, and market day activities. This synergy not only supports the economic independence of schools but also serves as a medium for character building, fostering students who are creative, independent, and possess noble character. Therefore, the implementation of Islamic leadership combined with entrepreneurial ethics is able to create a religious, productive, and competitive educational environment, thereby contributing significantly to the sustainable improvement of the quality of Islamic educational institutions.